2014
DOI: 10.1007/s13762-014-0509-z
|View full text |Cite
|
Sign up to set email alerts
|

Refuse-derived fuel classification in a mechanical–biological treatment plant and its valorization with techno-economic criteria

Abstract: Refuse-derived fuels (RDF) are a category of alternative fuels produced as byproducts from the process of waste management plants. RDF can be utilized for heat and power production, contributing to the waste hierarchy set by European Union. However, the need for standardization of RDF becomes gradually important in SouthEastern Europe, where the market for waste recovered fuels is under development. The application of certification and quality management schemes in the waste treatment and fuel production proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“… Sources : Dianda et al (2017), Garcés et al (2016), Kanna et al (2017), Marquard and Bahls AG (2015), McDonnell et al (2010), Oliva et al (2009), Rahman et al (2017), Speight (2019), Vandecasteele and Vermeulen (2011), Vounatsos et al (2013), Wang et al (2012), Wei et al (2014), Wu et al (2015), Yao et al (2018), and Zieri et al (2018). …”
Section: Resultsmentioning
confidence: 99%
“… Sources : Dianda et al (2017), Garcés et al (2016), Kanna et al (2017), Marquard and Bahls AG (2015), McDonnell et al (2010), Oliva et al (2009), Rahman et al (2017), Speight (2019), Vandecasteele and Vermeulen (2011), Vounatsos et al (2013), Wang et al (2012), Wei et al (2014), Wu et al (2015), Yao et al (2018), and Zieri et al (2018). …”
Section: Resultsmentioning
confidence: 99%
“…Refuse-derived fuel (RDF) is a fuel substitute derived from waste management facilities. The use of RDF for heat and power production adheres to the European Union's waste hierarchy [15]. Materials such as refuse-derived fuel (RDF) fractions are used as fuel in cement or combined heat and power (CHP) plants.…”
Section: Introductionmentioning
confidence: 99%
“…Some of previous studies described the thermal characterization and potential use of various RDF materials for energy applications. The results revealed that the RDF materials consisted of higher amount of volatile matter and lower fixed carbon content than parent solid waste to generate the energy for combustion applications [1,2,5,7,8,12,20,21] Combustion behavior of RDF materials was analyzed in detail using thermal analysis previously. It has been observed that combustion of RDF materials in air can speed up the combustion process, lowers the ignition temperature, makes the complete combustion more certain and promotes the thermal efficient burning of RDF materials [17].In addition, thermal analysis of solid fossil fuels (coal and its derivatives) demonstrated that the temperature for releasing volatiles was higher than RDF materials.…”
Section: Introductionmentioning
confidence: 99%